Partner selection in public goods experiments - Giorgio Coricelli; Dietmar Fehr; Gerlinde Fellner (Institute for Advanced Studies (IHS), 2004)
This paper studies the effect of introducing costly partner selection for the voluntary contribution to a public good. Subjects participate in six sequences of five rounds of a twoperson public good game in partner design. At the end of each sequence, subjects can select a new partner out of six group members. Unidirectional and bidirectional partner selection mechanisms are introduced and compared to controls with random partner rematching. Results demonstrate significantly higher cooperation in correspondence to unidirectional partner selection than to bidirectional selection and random rematching. Average monetary effort for being able to choose a partner is substantially high and remains stable.
Keywords: C91; D62; H41; 330; public goods; partner selection; experimental economics; Öffentliches Gut; Spieltheorie; Test; Theorie; Soziale Beziehungen